Energy requirement assessment and water turnover in Japanese college wrestlers using the doubly labeled water method - Sagayama, H.; Kondo, E.; Shiose, K.; Yamada, Y.; Motonage, K.; Ouchi, S.; Osawa, T.; Nakajima, K.; Takahashi, H.; Higaki, Y.; Tanaka, H. (Journal of Nutritional Science and Vitaminology, 2017)
Estimated energy requirements (EERs) are important for sports based on body weight classifications to aid in weight management. The basis for establishing EERs varies and includes self-reported energy intake (EI), predicted energy expenditure, and measured daily energy expenditure. Currently, however, no studies have been performed with male wrestlers using the highly accurate and precise doubly labeled water (DLW) method to estimate energy and fluid requirement. The primary aim of this study was to compare total energy expenditure (TEE), self-reported EI, and the difference in collegiate wrestlers during a normal training period using the DLW method. The secondary aims were to measure the water turnover and the physical activity level (PAL) of the athletes, and to examine the accuracy of two currently used equations to predict EER. Ten healthy males (age, 20.4±0.5 y) belonging to the East-Japan college league participated in this study. TEE was measured using the DLW method, and EI was assessed with self-reported dietary records for ~1 wk. There was a significant difference between TEE (17.9±2.5 MJ•d-1 [4,283±590 kcal•d-1]) and self-reported EI (14.4±3.3 MJ•d-1 [3,446±799 kcal•d-1]), a difference of 19%. The water turnover was 4.61±0.73 L•d-1. The measured PAL (2.6±0.3) was higher than two predicted values during the training season and thus the two EER prediction equations produced underestimated values relative to DLW. We found that previous EERs were underestimating requirements in collegiate wrestlers and that those estimates should be revised.